E'XCESS VOLUMES OF HEAVY OIL- STOCKS MIXTURES+ (KEROSENE OR XYLENE) AT 3O3 K - M. Al-Qamaje, Haidar (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
Binary mixtures of three heavy oil-stocks had been subjected to density measurments. The data had been aquired on the volumetric behaviour of these systems. The heavy oil-stocks used were of good varity, namely 40 stock , 60 stock, and 150 stock, 40 stock is the lightest one with the API gravity 33.7 while 60 stock is middle type and 150 stock is heavy one, with API gravity 27.7 and 23.8 respectively. Stocks with Kerosene or Xylene for non-ideal mixtures for which excess volume can be positive or  negative. Mixture of heavy-oil stocks with paraffinic spike (Kerosene) show negative excess volume. While, aromatic rings results a lower positive excess volume, as shown in Xylene when blending with 40 stock and 60 stock but a negative excess volume when blending with 150 stock. The gravity of oil-stocks has an effect on excess volume when the oil-stocks spiked with Kerosene or Xylene. Those, 40 stock as typical light type resulted in minimum negative excess volume of -2.18, when it was spiked with the Kerosene, while the spiked heavy oil-stock with Kerosene gave a maximum excess volume of -11.2 The Redlich-Kister equation was used to fit the excess volume values, and the coefficients and estimate of the standard error values were presented.